Teachers’ Pedagogical Skill Profile in the Digital Learning Era: A Reflective Study in an Integrated Islamic Education Foundation - Rita Anggorowati; Irwan Gunawan (Jurnal Inovasi Pendidikan dan Sains, 2025)
The transformation of education in the digital era demands that teachers possess adaptive, innovative, and responsive pedagogical skills aligned with 21st-century learning needs. This study aims to analyse the profile of teachers’ pedagogical skills in the context of digital learning and to identify areas requiring further development. Employing a descriptive survey approach, the research involved 42 teachers from various educational levels (early childhood, primary, and lower secondary) at the Banjar Uswatun Hasanah Foundation. Data were collected using a 60-item reflective survey instrument on pedagogical skills, rated on a 4-point Likert scale. The results indicate that teachers demonstrate strong communication and interpersonal relationship skills (M = 3.64–3.76) yet face challenges in integrating technology into instruction (M = 2.07–2.33) and implementing project-based learning (M = 2.81–2.83). Overall, the average level of pedagogical skill was categorized as good (M = 3.13; SD = 0.76). These findings highlight the urgency of teacher professional development programs that focus on digital literacy and instructional innovation to enhance teacher readiness in responding to the dynamics of digital learning within integrated Islamic education settings